ALE-ANCF modeling of the lowering process of a J-lay pipeline coupled with dynamic positioning. (1st February 2023) - Liu, Depeng; Ai, Shangmao; Sun, Liping; Guedes Soares, C.
Abstract: A novel structural dynamics model for the lowering process of a J-lay pipeline is established by combining the absolute nodal coordinate formula with the arbitrary Lagrangian–Eulerian description. The constraint on the top of the pipeline is introduced into the dynamic equation in the form of generalized coordinates by using a material transport boundary to simulate the lowering process of the top end of the pipeline. A mesh scheme is adopted to control the element length and prevent numerical disturbances. The accuracy of the material transport boundary and mesh scheme is verified for the case of a pendulum with a time-varying length. Then, a coupled analysis program is developed to investigate J-lay deployment by a vessel using dynamic positioning. The tensioner is modeled as a damper to adjust the pay-out speed of the upper end of the pipeline. The numerical analysis is carried out on an explanatory example of a 16-inch pipeline being laid at a 1000-m water depth. The results show that the lowering process strongly affects the dynamic characteristics of the touch-down zone. Highlights: A novel and feasible ALE-ANCF model is established for the offshore pipeline J-lay lowering process. A reasonable damping tensioner is developed for adjusting the pay-out speed. Investigation of the dynamic response by implementing the ALE-ANCF model coupling with the DP vessel. Study the effect of the lowering process on the dynamic behaviors of TDZ.